Ketamine Induces Lasting Antidepressant Effects by Modulating the NMDAR/CaMKII-Mediated Synaptic Plasticity of the Hippocampal Dentate Gyrus in Depressive Stroke Model. (24th April 2021) - Abdoulaye, Idriss Ali; Wu, Shan-shan; Chibaatar, Enkhmurun; Yu, Da-fan; Le, Kai; Cao, Xue-jin; Guo, Yi-jing
Abstract : Background . Ketamine has been shown to possess lasting antidepressant properties. However, studies of the mechanisms involved in its effects on poststroke depression are nonexistent. Methods . To investigate these mechanisms, Sprague-Dawley rats were treated with a single local dose of ketamine after middle cerebral artery occlusion and chronic unpredicted mild stress. The effects on the hippocampal dentate gyrus were analyzed through assessment of the N-methyl-D-aspartate receptor/calcium/calmodulin-dependent protein kinase II (NMDAR/CaMKII) pathway, synaptic plasticity, and behavioral tests. Results . Ketamine administration rapidly exerted significant and lasting improvements of depressive symptoms. The biochemical analysis showed rapid, selective upregulation and downregulation of the NMDAR2- β and NMDAR2- α subtypes as well as their downstream signaling proteins β -CaMKII and α -phosphorylation in the dentate gyrus, respectively. Furthermore, the colocalization analysis indicated a significant and selectively increased conjunction of β -CaMKII and postsynaptic density protein 95 (PSD95) coupled with a notable decrease in NMDAR2- β association with PSD95 after ketamine treatment. These changes translated into significant and extended synaptic plasticity in the dentate gyrus. Conclusions . These findings not only suggest that ketamine represents a viable candidate for the treatment of poststroke depression but also that ketamine's lasting antidepressant effects might be achieved through modulation of NMDAR/CaMKII-induced synaptic plasticity in key brain regions.